CLINICAL AND ELECTROCARDIOGRAPHIC ANALYSIS OF ACCELERATED IDIOVENTRICULAR RHYTHMS - T. V. Treshkur (Российский кардиологический журнал)
The aim of the work was to analyze 209 cases of accelerated idioventricular rhythms, after that we concluded with 4 types of an “interaction” of sinus node and ectopic pacemaker. The article is illustrated with 11 ECGs, among those rare phenomenon following the arrhythmia, and specifics of differential diagnosis.